Efektivitas Campuran Karbon Aktif Daun Nanas–Batubara dalam Peningkatan pH dan Penurunan Fe, Mn, serta TSS Air Asam Tambang PT Alreksa Bara Mitra - Ayu Ningtias; Lucia Litha Respati; Shalaho Dina Devy; Harjuni Hasan; Windhu Nugroho (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
Acid mine drainage (AMD) is characterized by low pH and high concentrations of heavy metals such as iron (Fe) and manganese (Mn) that exceed environmental quality standards, thus requiring effective treatment to prevent environmental pollution. This study aims to evaluate the ability of a mixture of activated carbon derived from pineapple leaves mixed with coal to increase pH and reduce Fe, Mn, and Total Suspended Solids (TSS) levels in acid mine drainage at PT Alreksa Bara Mitra. The process to make activated carbon involved preparation, carbonization, and activation processes on the pineapple leaves and coal separately. The following step is to mix but pineapple leaves and coal the has been activated. The treatment was conducted using an adsorption method with variations in adsorbent mass of 4 g, 8 g, and 12 g and a contact time of 30 minutes. The parameters analyzed included pH, Fe, Mn, and TSS before and after treatment, and the results were compared with the quality standards stipulated in Minister of Environment and Forestry Regulation No. 05/2022. The results showed that the characteristics of the activated carbon mixture met the SNI 06-3730-1995 standard. Increasing the adsorbent mass contributed to the rise in pH from 5.5 to near the acceptable range of 6–9 and significantly reduced Fe, Mn, and TSS concentrations below the permitted limits.The findings indicate that the mixture of pineapple leaf- and coal-based activated carbon is an effective, economical, and environmentally friendly alternative adsorbent for acid mine drainage treatment.